Is it safe to preserve the deltoid when resecting the proximal humerus for a primary malignant bone tumour?: A comparative study. (September 2017) - Cladière-Nassif, V.; Bourdet, C.; Audard, V.; Babinet, A.; Anract, P.; Biau, D.
Abstract : Aims: Resection of the proximal humerus for the primary malignant bone tumour sometimes requires en bloc resection of the deltoid. However, there is no information in the literature which helps a surgeon decide whether to preserve the deltoid or not. The aim of this study was to determine whether retaining the deltoid at the time of resection would increase the rate of local recurrence. We also sought to identify the variables that persuade expert surgeons to choose a deltoid sparing rather than deltoid resecting procedure. Patients and Methods: We reviewed 45 patients who had undergone resection of a primary malignant tumour of the proximal humerus. There were 29 in the deltoid sparing group and 16 in the deltoid resecting group. Imaging studies were reviewed to assess tumour extension and soft-tissue involvement. The presence of a fat rim separating the tumour from the deltoid on MRI was particularly noted. The cumulative probability of local recurrence was calculated in a competing risk scenario. Results: There was no significant difference (adjusted p = 0.89) in the cumulative probability of local recurrence between the deltoid sparing (7%, 95% confidence interval (CI) 1 to 20) and the deltoid resecting group (26%, 95% CI 8 to 50). Patients were more likely to be selected for a deltoid sparing procedure if they presented with a small tumour (p = 0.0064) with less bone involvement (p = 0.032) and a continuous fat rim on MRI (p = 0.002) and if the axillary nerve could be identified (p = 0.037). Conclusion: A deltoid sparing procedure can provide good local control after resection of the proximal humerus for a primary malignant bone tumour. A smaller tumour, the presence of a continuous fat rim and the identification of the axillary nerve on pre-operative MRI will persuade surgeons to opt for a deltoid resecting procedure. Cite this article: Bone Joint J 2017;99-B:1244–9.